Risk-Based Information System Audit: A Literature Review and Its Implications in Accounting - Alexandro Munthe; Cherin Mahulae; Iskandar Muda (Indo Publishing, 2025)
This paper examines the concept of Risk-Based Information System Auditing (RBISA) and its implications within the field of accounting. As organizations increasingly rely on digital technologies and automated accounting systems, the demand for more adaptive and risk-oriented audit methodologies has grown substantially. Drawing from existing literature and established frameworks such as COBIT, ITAF, and COSO, this study explores how risk-based auditing enhances the reliability, efficiency, and integrity of financial information systems. The paper highlights the core principles of RBISA (risk identification, assessment, control testing, and reporting) and emphasizes its role in strengthening internal controls, improving audit efficiency, and supporting proactive risk management. Moreover, it discusses how technological tools such as data analytics and automated audit trails improve audit quality while also introducing new skill requirements for auditors. The findings suggest that RBISA contributes to improved governance, financial transparency, and compliance with regulatory standards. Ultimately, this study underscores the importance of integrating risk-based and technology-driven auditing approaches in modern accounting practices to enhance accountability and organizational resilience.